Preparation of Optically Pure Tertiary Phosphine Oxides via the Addition of P‑Stereogenic Secondary Phosphine Oxide to Activated Alkenes - Wang, Ji-Ping; Nie, Shao-Zhen; Zhou, Zhong-Yang; Ye, Jing-Jing; Wen, Jing-Hong; Zhao, Chang-Qiu (Journal of organic chemistry, 2016)
Functionalized P,C-stereogenic tertiary phosphine oxides were prepared by the addition of (R P)-menthyl phenylphosphine oxide to activated olefins, in high drP and drC, and were isolated in excellent yields. The reaction was readily catalyzed by Ca(OH)2 or occurred with gentle heating. A wide range of substrates, including vinyl ketones, esters, nitriles, and nitro alkenes, can be used in the reaction.